2022
DOI: 10.3390/met12071222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plastic Strain Control on Martensite Evolution and Fatigue Life of Metastable Austenitic Stainless Steel

Abstract: Metastable austenitic stainless steel was investigated during fatigue tests under strain control with either constant total or constant plastic strain amplitude. Two different material conditions with coarse-grained and ultrafine-grained microstructure were in focus. The influence of plastic strain control of the fatigue test on both the martensitic phase transformation as well as on the fatigue lives is discussed. In addition, an approach for calculating the Coffin–Manson–Basquin parameters to estimate fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In the crack initiation phase, a material can cyclically harden, soften, or exhibit an almost constant stress−strain response under cyclic loading. This depends, in part, on the material, the induced stress states, temperature, and type of fatigue test [26][27][28]. Corrosion-induced damage can have a substantial influence on crack initiation and early crack growth, which subsequently leads to fatigue failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the crack initiation phase, a material can cyclically harden, soften, or exhibit an almost constant stress−strain response under cyclic loading. This depends, in part, on the material, the induced stress states, temperature, and type of fatigue test [26][27][28]. Corrosion-induced damage can have a substantial influence on crack initiation and early crack growth, which subsequently leads to fatigue failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the increase in surface roughness after shot-peening may deteriorate the fatigue strength, the introduced residual compressive stress is able to increase the fatigue strength/life of 304 and/or 316 stainless steels (SSs) [15][16][17]. Strain-induced martensitic transformation may occur in metastable austenitic SSs during straining [18][19][20] and, in a severely shot-peened layer, austenite to martensite transformation may also occur [2,5]. It is reported that huge numbers of dislocations are found in the lath martensite within the nano-grained region [2].…”
Section: Introductionmentioning
confidence: 99%